Integration of Semantic Approaches in Arabic Mufradat Learning at Pesantren Mamba'ul Ulum Turen Malang - Makinuddin, Mohammad; Rosyida, Asmaa (Yayasan Mutiara Hati Moeslem, 2025)
This study explores the integration of semantic approaches in teaching Arabic vocabulary (mufradat) at Pondok Pesantren Mamba’ul Ulum Turen Malang, aiming to enhance students’ understanding of word meanings within contextual and cultural frameworks. Employing a qualitative phenomenological method, data were collected through in-depth interviews, participant observations, and documentation involving students and teachers. Findings reveal that semantic approaches improve students’ comprehension by linking words to real-life contexts and cultural values, fostering a deeper and more meaningful acquisition beyond rote memorization. Despite challenges such as ambiguous word meanings, limited learning resources, and varying teacher competencies, the approach effectively enriches lexical and grammatical knowledge and strengthens communication skills in religious and social settings. Unique teaching practices incorporating authentic religious texts and collaborative semantic analysis further support this integration. Moreover, cultural meanings embedded in vocabulary connect language learning to the students’ social and religious identity, highlighting the importance of culturally responsive pedagogy. This research concludes that semantic-based teaching not only enhances language competence but also nurtures critical thinking and spiritual development, providing a comprehensive model for Arabic language education in pesantren contexts.